Delegation, promotion, and manager selection - Benjamin Häusinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Promotions serve two purposes. They ought to provide incentives for employees and to select the best employee for a management position. However, if non-contractible managerial decision rights give rise to private benefits and preference misalignment between managers and the firm, these two purposes are in conflict. This is because the worker with the largest private benefit as a manager has the strongest incentives to work hard to get promoted. This article shows how the interplay of managerial decision rights and performance-based promotions leads to a situation often referred to as the Peter principle: employees that create lower expected profits as managers have yet better promotion prospects. That finding still holds when the firm owner optimally chooses the promotion rule, the degree of delegation, and wage payments to both employees and managers. To optimize organizational design, the firm balances better worker incentivization but worse manager selection by using performance-based promotions and restricting managerial decision rights.
Keywords: D2; L22; M51; M52; 330; Peter Principle; Promotion; Delegation of Decision Rights; Incentives; Manager Selection; Organizational Design